2021
DOI: 10.1007/s12571-021-01215-2
|View full text |Cite
|
Sign up to set email alerts
|

Do agri-food market incentives improve food security and nutrition indicators? a microsimulation evaluation for Kenya

Abstract: The sustainable development goal #2 aims at ending hunger and malnutrition by 2030. Given the numbers of food insecure and malnourished people on the rise, the heterogeneity of nutritional statuses and needs, and the even worse context of COVID-19 pandemic, this has become an urgent challenge for food-related policies. This paper provides a comprehensive microsimulation approach to evaluate economic policies on food access, sufficiency (energy) and adequacy (protein, fat, carbohydrate) at household level. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Guided by previous work by Marivoet et al (2020) and Ramos et al (2021) on the obstacles to affordability and the potential gains in reducing transaction costs, three simulations (Sim) were undertaken: Sim 1: 20% total factor productivity (TFP) increase on all focus ASF commodities (eggs, milk, chicken and beef).Given the inelastic nature of supply and demand, it is expected that the increase in availability through more supply would put more pressure and yield lower prices and make ASF more affordable. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guided by previous work by Marivoet et al (2020) and Ramos et al (2021) on the obstacles to affordability and the potential gains in reducing transaction costs, three simulations (Sim) were undertaken: Sim 1: 20% total factor productivity (TFP) increase on all focus ASF commodities (eggs, milk, chicken and beef).Given the inelastic nature of supply and demand, it is expected that the increase in availability through more supply would put more pressure and yield lower prices and make ASF more affordable. …”
Section: Methodsmentioning
confidence: 99%
“…To do this, we used a dynamic computable general equilibrium (CGE) model of the Kenyan economy calibrated to a 2018 Social Accounting Matrix (SAM). Our approach expands on previous studies (Ramos et al, 2021 ) by looking at the production level of the supply chain. As outcomes, we consider availability, price, consumption and welfare (as measured by ‘Equivalent Variation (EV) in income’, explained in the next section).…”
Section: Introductionmentioning
confidence: 99%
“…, 2017). The absence of a well-functioning market limits household consumption and sustainable food production (Feyisa, 2021; Ramos et al. , 2021; Muller, 2009).…”
Section: Related Literaturementioning
confidence: 99%
“…In addition to socioeconomic endowment and behavioral practices, the market links farm income to household dietary diversity (Rajendran et al, 2017). The absence of a wellfunctioning market limits household consumption and sustainable food production (Feyisa, 2021;Ramos et al, 2021;Muller, 2009). A well-functioning input and output market thus allows farmers to specialize, which increases yields and crop sales (Ahmed, 2022;Barrett, 2008;Tesfay, 2020).…”
Section: Related Literaturementioning
confidence: 99%
“…Nutrition‐sensitive approaches to enhance food security, child care, and hygienic environmental and health services have shown the potential to mitigate the burden of child stunting (Ruel et al, 2018). Economic status can play a key role in improving nutritional quality in micronutrient intake and daily energy consumption by increasing purchasing power, particularly benefiting those most in poverty (Ramos et al, 2021). Previous literature analyzing the prevalence of child stunting and gross domestic production (GDP) per person in the country reported that a 10% increase in GDP per person predicts an almost 6% reduction in stunting among the ultrapoor population.…”
Section: Introductionmentioning
confidence: 99%